Host Molecules That Promote Pathophysiology of Ocular Herpes - Shukla, Sajal Deea; Valyi-Nagy, Tibor (Frontiers in Microbiology, 2022)
Herpes simplex virus type-1 (HSV-1) is a human virus that causes lifelong infections in a large population worldwide. Recurrence of HSV-1 from latency in trigeminal ganglion (TG) is the trigger of the morbidities seen with this virus. In addition to causing fever blisters and cold sores, occasionally the virus can also cause corneal lesions resulting in blindness in untreated individuals. Several host cell proteins play important roles in HSV-1 infection of the eye. HSV-1 enters into the corneal epithelial cells via its interactions with cell surface receptors. In parallel, the Toll-like receptors sense viral invasion and activate defense mechanisms to fight the infection. New data shows that Optineurin, a host autophagy receptor is also activated to degrade viral particles. In contrast, activation of heparanase, a host enzyme, induces an immune-inflammatory response, which triggers pro-inflammatory and pro-angiogenic environment and ultimately results in many of the clinical features seen with HSV-1 infection of the cornea. Rarely, HSV-1 can also spread to the central nervous system causing serious diseases. In this review, we summarize the latest knowledge on host molecules that promote pathophysiological aspects of ocular herpes.